AI Integration in Broadcast Production Management at Radio XChannel - Mulyani, Henny Sri; Basith, Achmad Abdul; Syafri, Bilhaq Sakti; Prasetyo, Ridho Danu (School of Journalism, Faculty of Communication Sciences, Universitas Padjadjaran, 2025)
The use of Artificial Intelligence (AI) in Indonesia has experienced rapid growth. As of early 2025, Indonesian users recorded over 300 million visits to AI applications, placing the country among the top ten globally in AI usage. Worldwide, 87% of organizations had adopted AI in at least one operational function, including within the radio broadcasting sector. Radio XChannel is one of the Indonesian radio stations that began integrating AI into its operations. This study aimed to explore the station’s AI adoption strategy and identify the opportunities and challenges faced during implementation. A qualitative method with a descriptive approach was employed. Data were collected through in-depth interviews and documentation of broadcast materials and internal policies related to AI. This study examines how AI is applied in XChannel, based on radio production management processes, and how AI can provide a different perspective. The research findings indicate that XChannel is starting to implement AI to adapt to digital disruption while also addressing the need for efficiency to meet the challenges of the radio business. However, the application of AI remains limited to text-to-audio conversion, playing the role of a news anchor in news segments. Meanwhile, AI is not yet utilized in the live broadcast process and is only employed in content production for the YouTube channel. These findings suggest that the use of AI in the radio industry, specifically at XChannel, is still in its early stages and faces both technical challenges and human resource constraints. Further research is recommended to explore more comprehensive AI integration strategies and evaluate their impact on audience engagement and the quality of the produced content.